Willingness to pay for quality attributes of fresh beef - Berges, Miriam; Casellas, Karina Susana; Rodriguez, Hector Ricardo; Errea, Damián (IAAE, 2018)
In recent decades, the demand for food worldwide has undergone significant changes that have highlighted the issue of the quality and safety of food consumed. After international food crisis associated with consumption of fresh meat, consumer concerns about the quality and safety of these products has been increased. However, the attributes for assessing the safety of fresh meat consumption are not directly observable; they are credence attributes. The aim of this work is to investigate consumers´ perceptions of safety in Argentina and identify factors that help explain consumers' willingness to pay for different attributes related safety of the beef products, including, a hypothetical hygiene certification in handling and retailing. The results indicate a positive willingness to pay for fresh meat attributes such as personalized attention in a butcher counter, the presence of a "safety certification" in the place of purchase and the bright red color on the product.